Sectoral concentration and regional specialisation of Small and Medium Enterprises (SMEs) in Russia: Application of Krugman Index - Pinkovetskaia, Iuliia (The journal of contemporary issues in business and government, 2017)
The purpose of this study was to assess the current levels of sectoral concentration and regional specialisation of Small and Medium Enterprises (SMEs) in Russia using Krugman’s Indexes of concentration and specialisation. The study used data from the official statistical observation of activities of all Russian SMEs for the year 2015, representing 82 Russian regions and 13 types of economic activity (sectors). A high level of SME concentration was observed in fishing, mining and quarrying and agricultural sectors. The concentration of SMEs in manufacturing is much higher than in the services sector. The regional specialisation of SMEs is relatively small in Russia. Specialisation is above the national average in the regions where agricultural SMEs dominate and in Moscow, where real estate SMEs are widely distributed. These results could be of interest to entrepreneurs when choosing the type of sectors to engage in and policymakers in promoting SMEs in particular economic sectors and regions of Russia.